Fermented or unfermented milk using Bifidobacterium animalis subsp. lactis HN019: Technological approach determines the probiotic modulation of mucosal cellular immunity - Bogsan, Cristina Stewart Bittencourt (2014)
Functional foods are important sources of probiotic delivery, mainly by fermentedmilk products. The physiological benefits attributed to bifido bacteria are their abilities to interfere with the adhesion of pathogenic species to surfaces of intestinal cells, and to enhance the host's immune function through their metabolic activities. However, the effects of a technological approach ? fermentation or addition of probiotic in milk, and its efficacy in health are rarely taken into consideration. Hence, fermented or unfermented milk using Bifidobacterium animalis subsp. lactis HN019 were administered to BALB/c mice for 14 days. After that, the architecture of the gut was histologically investigated, and the related immune cells were examined by flow cytometry and immunofluorescence. Increase in mucus and cellularity production, changes in immune pattern and preservation of mucosal epithelia in health BALB/c mice were observed only in the fermentedmilk group. This suggested that changes in functionality of bifidobacteria and/or themetabolites produced by the fermentation process are the keys to improving beneficial effects in the host of the gut mucosa.